Pediatric evidence the practice-changing studies - Carter, Lindsay P.; Eicken, Meredith G. A.; Madhavan, Vandana L. (Wolters Kluwer, 2016)
"The practice of pediatric medicine can feel very personal; there is an incomprehensible level of trust placed by parents in pediatric providers caring for their children and the enormity of this responsibility is felt by all"--Provided by publisher.